2010
DOI: 10.1111/j.1600-0412.2010.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat cerclage prolongs pregnancy in women with prolapsed membranes

Abstract: We evaluated repeat cerclage in women with prolapsed membranes. Twenty-two women with bulging membranes after primary cerclage were offered repeat cerclage; 11 chose a repeat cerclage and 11 chose bed rest. The median gestational age at delivery, birthweight and survival rates were significantly higher in the repeat cerclage group compared to the bed rest group (mean 26.8 weeks vs. 21.7 weeks, p= 0.04, mean birthweight 1180 g vs. 491 g, p= 0.01 odds ratio for survival 22.0, 95% CI, 2.1-236). Early repeat cercl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 6 publications
3
21
0
1
Order By: Relevance
“…Similar findings were reported in women with reinforcing cerclage after ultrasound evidence of prolapsing membranes [16]. Two studies reported a prolonged latency to delivery and live birth rate in women with reinforcing cerclage compared to a reference group of women without second cerclage placement following the finding of prolapsed membranes upon direct visualization [15, 17]. Although latency and live birth rates were increased in one study, all pregnancies ended in preterm birth <28 weeks gestation without the mention of neonatal outcomes [17].…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Similar findings were reported in women with reinforcing cerclage after ultrasound evidence of prolapsing membranes [16]. Two studies reported a prolonged latency to delivery and live birth rate in women with reinforcing cerclage compared to a reference group of women without second cerclage placement following the finding of prolapsed membranes upon direct visualization [15, 17]. Although latency and live birth rates were increased in one study, all pregnancies ended in preterm birth <28 weeks gestation without the mention of neonatal outcomes [17].…”
Section: Resultssupporting
confidence: 67%
“…Articles were excluded from this paper for the following reasons: 3 were review articles, 3 did not specifically report pregnancy outcome, 14 did not include patients with reinforcing cerclage placement during the study period, 4 articles focused on the topic of cerclage technique, 2 articles focused on cerclage complications such as infection and stromal erosion, 2 were case series of reinforcing cerclage without a reference group, and 1 publication was a study protocol without outcome results available. After exclusions, 4 remaining articles were included in this systematic review [1417]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations